An analysis of research topics in software engineering – 2006 - Cai, Kai-Yuan; Card, David (The Journal of systems and software, 2008)
This paper is the first in a new annual series whose goal is to answer the following question: what are the active research focuses within the field of software engineering? We considered 7 top journals and 7 top international conferences in software engineering and examined all the 691 papers published in these journals or presented at these conferences in 2006. Consequently, we have a number of findings. (1) Seventy-three percent of journal papers focus on 20% of subject indexes in software engineering, including Testing and Debugging (D.2.5), Management (D.2.9), and Software/Program Verification (D.2.4). (2) Eighty-nine percent of conference papers focus on 20% of subject indexes in software engineering, including Software/Program Verification (D.2.4), Testing and Debugging (D.2.5), and Design Tools and Techniques (D.2.2). (3) Seventy-seven percent of journal/conference papers focus on 20% of subject indexes in software engineering, including Testing and Debugging (D.2.5), Software/Program Verification (D.2.4), and Management (D.2.9). (4) The average number of references cited by a journal paper is about 33, whereas this number becomes around 24 for a conference paper.